Investigating the implications of the London Heathrow Airport expansion for the landside freight industry - Ryan Lee; Moayad Shammut; Julian Allen; Xing Gao; Tianren Yang; Mengqiu Cao (Logistics, 2021)
The air cargo industry is hugely important to national economies, trade, and development. Thus far, there has been limited research on the landside freight industry. Therefore, the purpose of this paper is to extend the understanding of how alterations in the air cargo industry impact on its landside freight counterpart. It also seeks to explore the potential opportunities and challenges this presents, as well as the measures that can be taken to mitigate unsustainable development for the landside freight industry. Semi-structured interviews were used to collect the views of key stakeholders, freight industry experts, and other professionals. Our findings show that, if the airport expansion went ahead, the opportunities would generally outweigh the challenges. Increased freight activities and other positive spinoffs would result in the long-term. Increased freight activities and employment were the prime positive implications. Conversely, increased delays due to congestion was the main negative implication. Measures suggested to mitigate the adverse effects of the London Heathrow Airport (LHR) expansion entailed strengthening of consolidation centre efforts, freight collaboration, intelligent booking systems, use of low-carbon technologies, smart scheduling for revising the timetabling of deliveries, and greater use of rail transport for air cargo. The research highlights novel insights regarding existing freight-related issues from industry and academic experts, and further thoughts in relation to increased cargo activities stemming from the LHR expansion.
Keywords: 650; logistics; freight transport; surface access; supply chain; air cargo; London Heathrow Airport expansion